Contribution of Malnutrition and Lack of Breast Feeding in Persistent Diarrhea in Children Under 2 Years of Age - Amna Ihsan, Saima Naureen, Rizwan Waseem, Tayyaba Noor,, Javeria Fatima, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diarrhea episode lasting for greater than 14 days is known as persistent diarrhea. Aim: To find the current extent of factors leading to persistent diarrhea. Methods: It was a cross sectional study. 100 children with persistent diarrhea were included. Then parents were asked for contributing factors which were malnutrition and lack of exclusive breast-feeding up to the first four months of life. Data was analyzed on SPSS 22. Results: The mean weight of infants was 10.01±2.41kg. The mean duration of diarrhea was 15.51±1.31days. Malnutrition was found in 79(79%) infants. Lack of exclusive breast-feeding up to 4months of life was observed in 63(63%) cases. Conclusion: The most common contributing factor of chronic diarrhea in infants is malnutrition and secondly lack of breast feeding. Keywords: Chronic diarrhea, infants, malnutrition, exclusive breast feeding.